Effects of post-lithography cleaning on the yield and performance of CVD graphene-based devices - de Araujo, Eduardo Nery Duarte; de Sousa, Thiago Alonso Stephan Lacerda; de Moura Guimarães, Luciano; Plentz, Flavio (Beilstein Journal of Nanotechnology, 2019)
The large-scale production of high-quality and clean graphene devices, aiming at technological applications, has been a great challenge over the last decade. This is due to the high affinity of graphene with polymers that are usually applied in standard lithography processes and that, inevitably, modify the electrical proprieties of graphene. By Raman spectroscopy and electrical-transport investigations, we correlate the room-temperature carrier mobility of graphene devices with the size of well-ordered domains in graphene. In addition, we show that the size of these well-ordered domains is highly influenced by post-photolithography cleaning processes. Finally, we show that by using poly(dimethylglutarimide) (PMGI) as a protection layer, the production yield of CVD graphene devices is enhanced. Conversely, their electrical properties are deteriorated as compared with devices fabricated by conventional production methods.
Keywords: CVD graphene; defects; mobility; well-ordered domain